Content analysis of fourth grade Bahasa Indonesia textbook on Aswaja generation and noble character of Madrasah Ibtidaiyah - Nur Sofwah Azzahro'; Petra Kristi Mulyani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study aimed to analyze the content analysis of the fourth-grade Bahasa Indonesia textbook on the Aswaja generation and the noble character of Madrasah Ibtidaiyah (MI). MI is a school level equivalent to elementary school under the auspices of the Ministry of Religious Affairs and based on Nahdlatul Ulama/NU (Islamic organization) values, and uses the vision of the aswaja generation and noble character as the establishment of the school (madrasah). While textbooks are the main tools in learning, they might not be written representations of school ideology. This study used a qualitative method of content analysis. The Bahasa Indonesia textbook was coded to look for themes representing the Aswaja generation and noble character indicators. An expert in NU validated the theme and indicators for the coding and the coding result. The results showed that the textbook reflected NU ideology, mostly on tolerance, patience, and helping others. Detailed values were discussed in the results. The research recommended future studies to analyze the representation of NU ideology when using the Bahasa Indonesia textbook in the classroom context.